Adherence to antiretroviral therapy and acceptability of planned treatment interruptions in HIV-infected children - Linda Harrison (2018)
There have been no paediatric randomised trials describing the effect of planned treatment interruptions (PTIs) of antiretroviral therapy (ART) on adherence, or evaluating acceptability of such a strategy. In PENTA 11, HIV-infected children were randomised to CD4-guided PTIs (n = 53) or continuous therapy (CT, n = 56). Carers, and children if appropriate, completed questionnaires on adherence to ART and acceptability of PTIs. There was no difference in reported adherence on ART between CT and PTI groups; non-adherence (reporting missed doses over the last 3 days or marking < 100 % adherence since the last clinical visit on a visual analogue scale) was 18 % (20/111) and 14 % (12/83) on carer questionnaires in the CT and PTI groups respectively (odds ratios, OR (95 % CI) = 1.04 (0.20, 5.41), χ 2 (1) = 0.003, p = 0.96). Carers in Europe/USA reported non-adherence more often (31/121, 26 %) than in Thailand (1/73, 1 %; OR (95 % CI) = 54.65 (3.68, 810.55), χ 2 (1) = 8.45, p = 0.004). The majority of families indicated they were happy to have further PTIs (carer: 23/36, 64 %; children: 8/13, 62 %), however many reported more clinic visits during PTI were a problem (carer: 15/36, 42 %; children: 6/12, 50 %). © 2012 The Author(s).